South Pacific sea surface temperature and global ocean circulation changes since the late Miocene - Antje Wegwerth; Helge W. Arz; Jérôme Kaiser; Gisela Winckler; Lester Lembke-Jene; Vincent Rigalleau; Nicoletta Ruggieri; Henrik Sadatzki; Frank Lamy (Nature Communications)
Abstract The Antarctic Circumpolar Current (ACC) is a major driver of global ocean circulation and climate. To better understand the interplay between long-term atmospheric and ocean variability in the Southern Ocean since the late Miocene, we present sea surface temperature (SST) and carbonate preservation records from the Subantarctic Eastern South Pacific (IODP Site U1543), along with an extended ACC strength record from Central South Pacific Site U1541. We focus on long-term eccentricity-scale variations showing decreased (increased) SST with enhanced (reduced) CaCO3 preservation, and stronger (weaker) ACC strength, particularly during the Pliocene. These changes coincide with stronger (weaker) South Pacific SST gradients, possible northward (southward) migration of Southern Ocean fronts, strengthened (weakened) westerlies, and atmospheric CO2 release. These patterns contrast with Pleistocene glacial-interglacial cycles. Reduced Pacific-Atlantic exchange through the Drake Passage may have weakened Atlantic Meridional Overturning Circulation during warming at Site U1543 across the intensification of Northern Hemisphere Glaciation. Simultaneous stronger ACC and higher CaCO3 deposition in the high-latitude Pacific suggest a strengthened basin-wide Pacific overturning circulation during parts of the Pliocene.